Análisis del comportamiento del rendimiento académico en matemáticas de los estudiantes de décimo año de Educación General Básica en la Unidad Educativa 'Central Técnico' mediante ANOVA Bootstrap. Implicaciones para la mejora continua. - López Rodríguez, Gustavo Javier (2024)
The present study focuses on investigating the academic performance of students in mathematics, addressing potential variations in their performance across the academic years 2020-2021, 2021-2022, and 2022-2023. The main objective is to analyze these differences using ANOVA Bootstrap, an advanced statistical technique that allows for robust comparisons of means across different groups. The research employed a quantitative approach, with an observational longitudinal trend design and a descriptive level of analysis. The methodology involved collecting student grade data, followed by a comprehensive statistical analysis using R software. ANOVA Bootstrap was applied to obtain accurate results regarding the observed variations. The findings indicate a downward trend in academic performance over the years analyzed, with significant differences identified between the groups. Based on these results, a set of strategies to improve academic performance in mathematics is proposed.